Effects of exercise training and creatine malate supplementation on ventilator threshold and anaerobic working capacity in long-distance runners - Tyka, A.; Palka, T.; Pilch, W.; Cebula, A.; Strzala, M.; Biel, A.; Pajor, P.; Tyka, A. (Journal of Kinesiology and Exercise Sciences, 2015)
Purpose. The aim of this study was to investigate the influence of a 6-week physical training programme and creatine malate supplementation on forming aerobic and anaerobic exercise capacity in long-distance runners in an experimental group (n = 7) and control group (n = 7). Basic procedures. The ventilatory threshold, the distance covered to the threshold, oxygen uptake per minute, heart rate, the percentage of maximal oxygen uptake, as well as the total distance, and maximal oxygen uptake were analysed. In a jumping test (single jump and a series of 15 jumps), total work and height of the gravity centre elevation were registered. Main findings. Only the experimental group showed a significant lengthening of the run distance to the ventilatory threshold and to the total distance, while in the jumping test (series of 15 jumps) an increase of anaerobic work was registered. Conclusions. Changes observed in runners suggest an ergogenic effect of creatine malate supplementation. In the control group, no significant changes in the analyzed variables were noted.